A Prior Magazine 15. - Wiarda, Andrea; Babias, Marius; Boomgaard, Jeroen; Geers, Kersten; Van Gelder, Hilde; Hlavajova, Maria; Laermans, Rudi; Roelstraete, Dieter; Szewczyk, Monika (Gent : KASK, vzw Mark, 2007)
Mannaerts, Valérie ; Rosler, Martha ; Sekula, Allan ; Loden, Barbara ; Steyerl, Hito
boek